Neutrophil to lymphocyte ratio may be used as a predictor in tendinopathy - Kaya, İsmail and Örsçelik, Aydan and Solmaz, İlker and Karaaslan, Burak and Yılmaz, Esra Şafak (The European Research Journal, 2023)
Objectives: Tendinopathy is a very common clinical disorder and a complex inflammation and degeneration process. Neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) have been studied and accepted as biomarkers of inflammation, predictors of progression and prognosis in several studies. We aimed to show that NLR and PLR levels can help predict prognosis for tendinopathy by comparing NLR and PLR levels of patients with tendinopathy with healthy control groups. Methods: Tendinopathy and healthy cases whose complete blood test was requested, were included in the study. Age, gender, white blood cell (WBC), neutrophil, lymphocyte, platelet counts, NLR and PLR of these cases were examined. Results: There is a statistically significant difference between the tendinopathy (n = 140) and control (n = 51) groups in WBC and NLR values (p < 0.001). One unit increase in WBC and NLR levels increases the risk of tendinopathy 1.74 and 10.616 times respectively. According to the results of the ROC analysis, the threshold value of the WBC and NLR values to increase the risk of tendinopathy is 6.47, and 1.64 respectively. Conclusions: Our study suggested NLR and WBC values are significant indicators of tendinopathy. We consider these results to be a guide for all physicians, especially sports medicine physicians.